TARI CALENGSAI DI KABUPATEN BANYUMAS REPRESENTASI SIMBOL STATUS ETNIS JAWA DAN ETNIS TIONGHOA - Eikka Sullistyaningsih (Institut Seni Indonesia Surakarta, 2015)
The goal of this research is to discover the form of the Calengsai dance by looking at theprocess through which the work was created. The artistic treatment or interpretation of theCalengsai dance uses Rahayu Panggah’s theory of Garap (interpretation), beginning with thematerial for interpretation and continuing through to the different considerations for interpretation. In order to reinforce the description about the representation of status symbols present in theCalengsai dance, Marvin Olsen’s concepts of Behavioural Interaction and Symbolic Interactionare used. The method used in writing this thesis is a qualitative method with an ethnochoreologicalapproach which uses an analytical descriptive form of discussion, presenting the data obtainedabout the creative ideas that emerge from the Calengsai dance through Calung, Lengger, andBarongsai. The process of artistic interpretation in the Calengsai dance and the representation ofstatus symbols present in the Calengsai dance can be seen from the analysis of the form of theCalengsai dance. The results of the research show that the role of the Calengsai dance in theBanyumas region is a status symbol for the ethnic Javanese and ethnic Chinese communitiesthrough Behavioural Interaction and Symbolic Interaction that are analyzed by looking at theform of the Calengsai dance.Keywords: Calengsai, Status Symbol, Dance.